2000
DOI: 10.1021/np990514f
|View full text |Cite
|
Sign up to set email alerts
|

Aminosterols from the Dogfish Shark Squalus acanthias

Abstract: Seven new aminosterols related to squalamine (8) were isolated from the liver of the dogfish shark Squalus acanthias. Their structures (1-7) were determined using spectroscopic methods, including 2D NMR and HRFABMS. These aminosterols possess a relatively invariant cholestane skeleton with a trans AB ring junction, a spermidine or spermine attached equatorially at C3, and a steroidal side-chain that may be sulfated. The structure of the lone spermine conjugate, 7 (MSI-1436), was confirmed by its synthesis from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 8 publications
3
106
0
Order By: Relevance
“…In addition to the active site-directed PTP1B inhibitors described above, there is also substantial interest in an allosteric PTP1B inhibitor trodusquemine (also known as MSI-1436; compound 6), which was discovered serendipitously. Trodusquemine was originally discovered among a family of aminosterol compounds in the tissues of dogfish shark with broad-spectrum antimicrobial activity as well as potent appetite suppressant and antidiabetic properties [106][107][108]. Subsequent investigation revealed that trodusquemine functioned as a potent noncompetitive inhibitor of PTP1B with a 200-fold preference (IC50 of 1 μM vs. 224 μM) over TCPTP [83].…”
Section: Ptp Inhibitorsmentioning
confidence: 99%
“…In addition to the active site-directed PTP1B inhibitors described above, there is also substantial interest in an allosteric PTP1B inhibitor trodusquemine (also known as MSI-1436; compound 6), which was discovered serendipitously. Trodusquemine was originally discovered among a family of aminosterol compounds in the tissues of dogfish shark with broad-spectrum antimicrobial activity as well as potent appetite suppressant and antidiabetic properties [106][107][108]. Subsequent investigation revealed that trodusquemine functioned as a potent noncompetitive inhibitor of PTP1B with a 200-fold preference (IC50 of 1 μM vs. 224 μM) over TCPTP [83].…”
Section: Ptp Inhibitorsmentioning
confidence: 99%
“…Primary amine oxidation and 7-OH sulfation of squalamine can produce PADS, suggesting that both compounds share biosynthetic pathways. The biosynthetic strategy that evolved in sea lamprey to produce an array of closely related aminosterol compounds with different biological functions seems to be similar to that found in sharks, in which squalamine and its analogs are produced (31,32).…”
Section: Discussionmentioning
confidence: 86%
“…There have been a few nonpeptide antimicrobial factors identified in fishes, in addition to squalamine and squalamine-related aminosterols from the sharks (32). A low molecular weight antimicrobial factor has been identified from channel catfish leukocytes (21).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Rao and co-workers isolated six other aminosterols (43)(44)(45)(46)(47)(48) from the liver of the dogfish shark ( Figure 4) [15]. The authors presented a very accurate spectral analysis based on 2D NMR (COSY, HETCOR, HMBC) as well as low-and high-resolution mass spectra (FAB, ESI, MALDI).…”
Section: Quaternary Alkylammonium Conjugates Of Steroidsmentioning
confidence: 99%
“…The steroid-polyamine conjugate was isolated from the liver tissues of the dogfish shark (Squalus acanthias) [11][12][13][14]. This aminosterol is a novel broad-spectrum antibiotic and exhibits a biocidal activity against Gram-positive and Gram-negative bacteria, fungi, protozoa, and viruses [15][16][17][18][19][20][21][22][23]. The antimicrobial activity of the squalamine has inspired work to design and synthesize new derivatives of steroidal-polyamine conjugates [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%